2007
DOI: 10.1111/j.1463-1318.2006.01180.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow up of patients with colorectal polyps: are the BSG guidelines being adhered to?

Abstract: These data have major implications with regard to patient safety, service provision and cost to the NHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…Pickard et al. demonstrated in their review that only 14.8% of patients were on the waiting list in accordance with the BSG guidelines [9]. Our results are similar, finding the figure to be 10%.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Pickard et al. demonstrated in their review that only 14.8% of patients were on the waiting list in accordance with the BSG guidelines [9]. Our results are similar, finding the figure to be 10%.…”
Section: Discussionsupporting
confidence: 87%
“…Mysliwiec et al demonstrated that some surveillance colonoscopy is inappropriately performed, and in excess of guidelines, particularly in the case of hyperplastic polyps and low-risk lesions such as a small adenoma [7], indeed a retrospective review of all colonoscopies carried out in a 3-month period by Thomas et al has shown that strict adherence to the guidelines would have caused a 47% reduction in surveillance colonoscopies [8]. Pickard et al demonstrated in their review that only 14.8% of patients were on the waiting list in accordance with the BSG guidelines [9]. Our results are similar, finding the figure to be 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines are followed inconsistently in a wide range of clinical circumstances. 15,16 In the NHS the impact of other NPSA safety alerts has been inconsistent. 17,18 The reasons for alerts and guidelines not being adopted are complex.…”
Section: Possible Solutionsmentioning
confidence: 99%
“…A growing body of data suggests that gastroenterologists often recommend repeat colonoscopy for colonic polyp surveillance more frequently than guidelines recommend [26]. Overuse of colonoscopy for polyp surveillance poses a significant economic burden, [7] may contribute to decreased colonoscopy capacity for initial screening, and increases the risk of complications [8, 9].…”
Section: Introductionmentioning
confidence: 99%